The Politics of Vaccination A Global History - Holmberg, Christine; Blume, Stuart; Greenough, Paul (Social Histories of Medicine, 2017)
Mass vaccination campaigns are political projects that presume to protect individuals, communities, and societies. Like other pervasive expressions of state power - taxing, policing, conscripting - mass vaccination arouses anxiety in some people but sentiments of civic duty and shared solidarity in others. This collection of essays gives a comparative overview of vaccination at different times, in widely different places and under different types of political regime.Core themes in the chapters include immunisation as an element of state formation; citizens' articulation of seeing (or not seeing) their needs incorporated into public health practice; allegations that donors of development aid have too much influence on third-world health policies; and an ideological shift that regards vaccines more as profitable commodities than as essential tools of public health. A novel lens through which to view changes in concepts of 'society' and 'nation' over time.